Construction of 2D/2D MoS2/g-C3N4 Heterostructures for Photoreduction of Cr (VI) - Wang, Chuanjie (Langmuir : the ACS journal of surfaces and colloids, 2021)
2D/2D MoS2/g-C3N4 (MCN) surface heterostructures were created by second thermal polymerization of bulk g-C3N4 and the reaction of thiourea and MoO3 at 670 °C. MoS2 networks grew vertically along the (002) facet on superior thin g-C3N4 nanosheets. The layered heterostructures drastically improved the Cr(VI) removal ability. In the dark case, 27% of Cr(VI) was removed within 45 min. The result indicates that the adsorption of Cr(VI) was a chemical adsorption process involving the sharing and transfer of electrons. The equilibrium data indicate that the adsorbent was covered with a monolayer adsorbate, which conformed to the Langmuir isotherm model (R2 = 0.9618). In addition, MCN nanocomposites could convert Cr(VI) into non-toxic Cr(III) by photoreduction under visible light irradiation. With an optimized composition, 100% of Cr(VI) was removed within 30 min, which was ∼10 times quicker compared with Cr(VI) removal under dark conditions. Because g-C3N4 nanosheets (sample CN670) with higher photocurrent density revealed the lowest photoreduction Cr(VI) ability, adsorption plays an important role in Cr(VI) removal. For MoS2/g-C3N4 nanocomposites used in Cr(VI) removal, adsorption and photoreduction were incorporated together to get excellent performance